2014
DOI: 10.1364/ao.53.006058
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of restraining ripple error on surface for optical fabrication

Abstract: The influence from the ripple error to the high imaging quality is effectively reduced by restraining the ripple height. A method based on the process parameters and the surface error distribution is designed to suppress the ripple height in this paper. The generating mechanism of the ripple error is analyzed by polishing theory with uniform removal character. The relation between the processing parameters (removal functions, pitch of path, and dwell time) and the ripple error is discussed through simulations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Power Spectral Density (PSD) character curves have been proposed to evaluate the errors of different frequency ranges [5]. Surface profile error and surface roughness are primarily compensated for by modifying the dwell time of optimization [6,7] and the convolution of the removal function, which are strongly related to the polishing strategy [8,9]; even the most difficult processing issues of edge mis-figure can be controlled [10,11]. Researchers have conducted comprehensive studies on this topic, and suggested that the surface profile error can be diminished through small-tool polishing [12], magneto-rheological finishing [13][14][15], and stressed lap polishing [16].…”
Section: Introductionmentioning
confidence: 99%
“…Power Spectral Density (PSD) character curves have been proposed to evaluate the errors of different frequency ranges [5]. Surface profile error and surface roughness are primarily compensated for by modifying the dwell time of optimization [6,7] and the convolution of the removal function, which are strongly related to the polishing strategy [8,9]; even the most difficult processing issues of edge mis-figure can be controlled [10,11]. Researchers have conducted comprehensive studies on this topic, and suggested that the surface profile error can be diminished through small-tool polishing [12], magneto-rheological finishing [13][14][15], and stressed lap polishing [16].…”
Section: Introductionmentioning
confidence: 99%